Environmental controls on benthic food web functions and carbon resource use in subarctic lakes. (14th January 2019) - Kivilä, E. Henriikka; Luoto, Tomi P.; Rantala, Marttiina V.; Kiljunen, Mikko; Rautio, Milla; Nevalainen, Liisa
Abstract: Climate warming and consequent greening of subarctic landscapes increase the availability of organic carbon to the detrital food webs in aquatic ecosystems. This may cause important shifts in ecosystem functioning through the functional feeding patterns of benthic organisms that rely differently on climatically altered carbon resources. Twenty‐five subarctic lakes in Finnish Lapland across a tree line ecotone were analysed for limnological and optical variables, carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope (SI) composition of surface sediment organic matter (OM) and fossil Chironomidae (Diptera) remains to examine environmental controls behind chironomid functional feeding group (FFG) structure and their isotopic associations for assessing ecosystem functioning and carbon utilisation. We hypothesise that the chironomid SI signatures reflect increased allochthony with increasing allochthonous input, but the resource use may be altered by the functional characteristics of the assemblage. Multivariate analyses indicated that carbon geochemistry in the sediments (δ 13 C, δ 15 N, C/N), nutrients, indices of productivity (chlorophyll‐ a ) and lake water optical properties, related to increasing presence of OM, played a key role in defining the chironomid FFG composition and isotopic signatures. Response modelling was used to examine how individual FFGs respond to environmental gradients. They showed divergent responses for OM quantity, dissolved organic carbon and nutrients between feeding strategies, suggesting that detritivores and filter feeders prefer contrasting carbon and nutrient conditions, and may thus hold paleoecological indicator potential to identify changes between different carbon fluxes. Benthic production was the primary carbon source for the chironomid assemblages according to a three‐source SI mixing model, whereas pelagic and terrestrial components contributed less. Between‐lake variability in source utilisation was high and controlled primarily by allochthonous OM inputs. Combination of biogeochemical modelling and functional classification is useful to widen our understanding of subarctic lake ecosystem functions and responses to climate‐driven changes in limnology and catchment characteristics for long‐term environmental change assessments and functional paleoecology.